Development of Multimodal Mathematics and Indonesian Language Books for Elementary School Learning in Bandung Barat - Ratna Sariningsih; Indra Permana; Ajeng Rena Fujirahayu (STAI Hubbulwathan Duri, 2023)
This study aims to (1) develop multimodal mathematics and Indonesian language books for learning in elementary schools, (2) determine the feasibility level of multimodal mathematics and Indonesian books for learning in elementary schools. This study used the Borg and Gall development model research method which consisted of (1) preliminary study, (2) initial product development, (3) expert validation and product revision, (4) limited field trials and product revision, (5) test try the field and the final product. The resulting product is an Android-based learning media in the form of multimodal books for learning mathematics and Indonesian in elementary schools with the subject, integer arithmetic operations, mixed integer arithmetic operations, determining mixed arithmetic operations with whole numbers, looking for main ideas and writing poetry in elementary schools. Based on the formulation of the problem, research results, and discussion, the results of this study can be concluded that (1) the development of Multimodal Book considered several product characteristics, namely, (a) students play an active role, (b) precise and consistent language, (c) music selection, background, buttons, types, colors, attractive letters, (d) animations and images support elementary school students' understanding, (2) multimodal Mathematics and Indonesian Language Books for Elementary School Learning are appropriate to use and can improve the learning of Mathematics and Indonesian Language for Elementary School students in West Bandung Regency.